Role of high-dose chemotherapy with hemopoietic stem cell transplantation in the treatment of multiple myeloma - S. V. Minenko; A. Yu. Popov; N. V. Zhukov; O. M. Votyakova; V. V. Ptushkin (Онкогематология)
Treatment results in a group of patients with multiple myeloma (n=18) treated with melfalan (200 mg/m2) followed by autologous peripheral blood stem cell transplantation as a second-line therapy are presented. Thirteen patients received one course of high-dose chemotherapy (HDCT), 5 had 2 courses. Before HDCT all treated patients achieved a partial remission (15 patients after 3 courses VAD, 3 patients after 3 courses of VAD and 2 courses of velcade- doxorubicin- prednisolone). The median time to disease progression was 33.1 (range 26—40) months; that of overall survival was 55.4 (range 29— 40) months.